QRS duration as an independent risk factor for appropriate shocks and mortality in patients with prophylactic implantable cardioverter-defibrillator. (19th May 2022) - Bengel, PRF; Kessel, B; Schloegl, S; Bauer, A; Junttila, J; Lubinski, A; Malik, M; Merkely, B; Schmidt, G; Svendsen, JH; Vos, MA; Willems, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Community's 7th Framework Programme FP7/2007-2013 Background: The implantable cardioverter defibrillator (ICD) is an established therapy for the prevention of sudden cardiac death (SCD) in high-risk heart failure patients. However, improvements in risk stratification are necessary to increase the efficiency of ICD use. We performed an analysis of the retrospective EU-CERT-ICD registry with respect to QRS duration and effects of cardiac resynchronisation therapy (CRT) on outcomes. Methods/Results: A total of 5033 patients (81% males) from 14 European centres had an ICD implanted for primary prophylaxis. Mean age at the time of ICD implantation was 64±11 years and ischemic cardiomyopathy was the underlying pathology in 65% of patients. CRT was used in 43% of the patients. The median follow-up was 2.7 years (IQR 1.4-4.6 years). Predefined primary endpoints were all-cause mortality, first appropriate and first inappropriate shocks. The effect of covariates on the cumulative primary endpoints were assessed through hazard ratios in the Fine and Gray subdistributional hazard models (accounting for the competing risks) stratified by centres. Because of resynchronization by the device, the analysis considered a different influence of QRS on outcomes in the CRT-D and the ICD groups. We observed an increase in the cumulative incidence of the first appropriate shock with increasing QRS values for patients implanted with only an ICD (HR 1.12 per 10ms increase, p<0.001). In patients with CRT-D, increasing QRS values related to a (statistically non-significant) decrease in the cumulative incidence of the first appropriate shocks (HR 0.96 per 10ms, p=0.299). Since a wide QRS is an indication for CRT-D therapy, high QRS values cluster among those patients with implanted CRT-D, while among patients with QRS under 130ms standard ICD implantations are more frequent. This can explain the observed increase in the cumulative incidence of the first appropriate shocks for increasing QRS values up to 130ms in the ICD-group and its decrease for increasing QRS values over 130ms in the CRT-D group. Regarding all-cause mortality, hazard ratios for age, LVEF, NYHA, ICM, AF, diabetes and sex category agreed with the results obtained in previously published meta-analyses. Increased QRS values are associated with higher mortality in the ICD group (HR 1.09 per 10ms increase, p<0.001), but not in the CRT-D group (HR 0.99 per 10ms increase, p=0.695). Conclusion: In our study, we confirmed QRS duration as an independent risk factor for appropriate ICD shocks and all-cause mortality in patients with ICD for primary prophylaxis. However, this was only observed in patients with single- or dual-chamber ICD, while there was no correlation in CRT-D patients. The findings suggest that CRT-D exerts a protective effect regarding the occurrence of first appropriate shock and all-cause mortality for patients with QRS values higher than 130 ms and indication for resynchronization.